2009
DOI: 10.1016/j.socscimed.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, gender and cardiovascular mortality: Behavioural, psychological distress and metabolic explanations

Abstract: The intermediate processes through which the various unmarried states can increase the risk of subsequent cardiovascular disease mortality are incompletely understood. An understanding of these processes and how they may vary by gender is important for understanding why marital status is strongly and robustly associated with subsequent cardiovascular disease. In a prospective study of 13,889 Scottish men and women (mean age 52.3, Standard Deviation: 11.8 yrs, range 35–95, 56.1% female) without a history of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 31 publications
(29 reference statements)
14
135
2
5
Order By: Relevance
“…24 In general, although socioeconomic status and substance abuse appeared to play a role in the worsened outcomes of unmarried patients, these factors did not explain all of the differences. 14,23,24 could explain the lower mortality rate of married men and would be consistent with prior data demonstrating improved mortality associated with more rapid initiation of antibiotic therapy. 10 These results also suggest that lives could be saved by educating patients at risk for pneumonia to seek treatment early when they develop suggestive symptoms, as has been suggested by Ewig and Torres, 21 similar to campaigns teaching patients to avoid delays in treatment if they develop symptoms suggesting myocardial infarction or stroke.…”
Section: Baseline Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…24 In general, although socioeconomic status and substance abuse appeared to play a role in the worsened outcomes of unmarried patients, these factors did not explain all of the differences. 14,23,24 could explain the lower mortality rate of married men and would be consistent with prior data demonstrating improved mortality associated with more rapid initiation of antibiotic therapy. 10 These results also suggest that lives could be saved by educating patients at risk for pneumonia to seek treatment early when they develop suggestive symptoms, as has been suggested by Ewig and Torres, 21 similar to campaigns teaching patients to avoid delays in treatment if they develop symptoms suggesting myocardial infarction or stroke.…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…Married patients had a signifi cantly lower in-hospital mortality rate (9.4% vs 10.6%, study of outcomes of sepsis, in which patients with a pulmonary source composed approximately 45%, single patients had a higher incidence and higher risk-adjusted hospital mortality rate compared with married and widowed patients. 22 There have also been several studies on the effect of marital status on the outcomes of conditions such as cardiovascular disease, 23 lung cancer, 24 and heart failure. 14 In some studies, all categories of unmarried men did worse, 14 whereas in others only specifi c subcategories, such as widowed men, did worse.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…4,9,10,[15][16][17][18][19][20] We grouped patients who were separated, divorced, or widowed based on publications suggesting that this group was often at a higher risk for CV events. 9,[19][20][21][22][23][24] The primary outcome of this analysis was MACE 4 at 15 months, defined as a composite of all-cause death, repeat MI, stroke, or urgent coronary revascularization (UCR). The outcomes for MI and stroke were reported as first fatal or nonfatal events.…”
Section: Methodsmentioning
confidence: 99%
“…In married vs unmarried men and women, past studies highlighted differences in outcomes following an MI. 21,24,25,[29][30][31] It was observed that women receive less informal caregiver support than do men, with worse outcomes, 1 to 12 months following an MI. 25 However, in contrast with many of the prior studies that controlled simply for certain socioeconomic determinants of health, such as income and education, we additionally adjusted for differences in baseline comorbidities that may have attenuated any association with marital status.…”
Section: Following Logistic Regression and Cox Proportional Hazarmentioning
confidence: 99%
“…Также доказано, что женатые мужчины испытывают меньший уровень эмоционального стресса и ведут более здоровый образ жизни по сравнению с одинокими мужчинами [15]. В то же время считается, что замужние женщины имеют более высокий уровень стресса, связанный с семейной жизнью.…”
Section: таблицаunclassified